Past, Present, and Future of Molecular and Cellular Oncology - Galluzzi, Lorenzo; Vitale, Ilio; Kroemer, Guido (Frontiers in Oncology, 2011)
In the last twenty years, the field of cellular and molecular oncology has been born and has moved its first steps, with an increasingly rapid pace. Hundreds of oncogenic and oncosuppressive signaling cascades have been characterized, facilitating the development of an ever more refined and variegated arsenal of diagnostic and therapeutic weapons. Furthermore, several cancer-specific features and processes have been identified that constitute promising therapeutic targets. For instance, it has been demonstrated that microRNAs can play a critical role in oncogenesis and tumor suppression. Moreover, it turned out that tumor cells frequently exhibit an extensive metabolic rewiring, can behave in a stem cell-like fashion (and hence sustain tumor growth), often constitutively activate stress response pathways that allow them to survive, can react to therapy by engaging in non-apoptotic cell death programs, and sometimes die while eliciting a tumor-specific immune response. In this Perspective article, we discuss the main issues generated by these discoveries that will be in the limelight of molecular and cellular oncology research for the next, hopefully few years.